2014
DOI: 10.1111/pere.12056
|View full text |Cite
|
Sign up to set email alerts
|

A prototype analysis of infidelity

Abstract: The current research tested whether the concept of infidelity is prototypically organized and whether laypeople's conceptualizations of infidelity are consistent with how researchers have operationalized this construct. Across 4 studies, results indicated that infidelity is indeed prototypically organized as individuals are able to list and rate how central certain features are to the infidelity construct. Furthermore, there was evidence that the centrality ratings influenced how individuals processed informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
24
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 53 publications
(103 reference statements)
4
24
0
2
Order By: Relevance
“…Furthermore, participants were able to define for themselves whether they engaged in infidelity or not, so our operationalization of infidelity is somewhat subjective. Future work could benefit by more precisely defining infidelity for participants, although there is difficulty in defining infidelity for participants as both laypeople and researchers possess broad and varying definitions of infidelity (see Weiser et al, , for discussion). Moreover, more detail about parental infidelity could also be collected to explore for moderators (e.g., offspring's reactions to parental infidelity, type of parental infidelity).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, participants were able to define for themselves whether they engaged in infidelity or not, so our operationalization of infidelity is somewhat subjective. Future work could benefit by more precisely defining infidelity for participants, although there is difficulty in defining infidelity for participants as both laypeople and researchers possess broad and varying definitions of infidelity (see Weiser et al, , for discussion). Moreover, more detail about parental infidelity could also be collected to explore for moderators (e.g., offspring's reactions to parental infidelity, type of parental infidelity).…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have focused on the presence of specific behaviors such as flirting, kissing, and sexual intercourse (Luo, Cartun, & Snider, 2010). In a recent prototype analysis, Weiser, Lalasz, Weigel, and Evans (2014) found that laypeople tend to focus less on the presence of specific behaviors and instead conceptualize infidelity in terms of the concealment of behaviors and the resulting emotional fallout. In the United States, infidelity is particularly viewed as unacceptable for romantic relationships (Druckerman, 2007;Wiederman & Allgeier, 1996), likely due to its often-hurtful nature.…”
mentioning
confidence: 99%
“…Previous prototype analyses describe a series of studies approach extending from three studies (Hone et al, ) to seven studies (Lambert et al, ). The key characteristics of five prototype analyses (Fehr and Sprecher, ; Hone et al, ; Kearns and Fincham, ; Lambert et al, ; Weiser et al, ) are illustrated in Appendix S1, Supporting information.…”
Section: Introductionmentioning
confidence: 99%
“…As this number of attributes resembles the total number of attributes generated for other common everyday constructs (e.g., love and commitment, n = 68 and 40 features respectively, Fehr, 1988; forgiveness, n = 78 features, Kearns & Fincham, 2004; infidelity, n = 95 features, Weiser et al, 2014), findings suggest that mental toughness is a familiar term to laypeople.…”
Section: Overall Discussionmentioning
confidence: 64%